Impact of hospital characteristics on implementation of a Pediatric Early Warning System in resource-limited cancer hospitals - Abutineh, Farris; Graetz, Dylan E.; Muniz-Talavera, Hilmarie; Ferrara, Gia; Puerto-Torres, Maria; Chen, Yichen; Gillipelli, Srinithya R.; Elish, Paul; Gonzalez-Ruiz, Alejandra; Alfonso Carreras, Yvania; Alvarez, Shillel; Arce Cabrera, Daniela; et al. (Frontiers in Oncology, 2023)
Pediatric Early Warning Systems (PEWS) aid in identification of deterioration in hospitalized children with cancer but are underutilized in resource-limited settings. Proyecto EVAT is a multicenter quality improvement (QI) collaborative in Latin America to implement PEWS. This study investigates the relationship between hospital characteristics and time required for PEWS implementation. This convergent mixed-methods study included 23 Proyecto EVAT childhood cancer centers; 5 hospitals representing quick and slow implementers were selected for qualitative analysis. Semi-structured interviews were conducted with 71 stakeholders involved in PEWS implementation. Interviews were recorded, transcribed and translated to English, then coded using a priori and novel codes. Thematic content analysis explored the impact of hospital characteristics and QI experience on time required for PEWS implementation and was supplemented by quantitative analysis exploring the relationship between hospital characteristics and implementation time. In both quantitative and qualitative analysis, material and human resources to support PEWS significantly impacted time to implementation. Lack of resources produced various obstacles that extended time necessary for centers to achieve successful implementation. Hospital characteristics, such as funding structure and type, influenced PEWS implementation time by determining their resource-availability. Prior hospital or implementation leader experience with QI, however, helped facilitate implementation by assisting implementers predict and overcome resource-related challenges. Hospital characteristics impact time required to implement PEWS in resource-limited childhood cancer centers; however, prior QI experience helps anticipate and adapt to resource challenges and more quickly implement PEWS. QI training should be a component of strategies to scale-up use of evidence-based interventions like PEWS in resource-limited settings.